Trauma exposure and stress‐related disorders in African‐American women with diabetes mellitus. Issue 2 (14th January 2020) - Dixon, H. Drew; Michopoulos, Vasiliki; Gluck, Rachel L.; Mendoza, Hadrian; Munoz, Adam P.; Wilson, Joseph G.; Powers, Abigail; Schwartz, Ann C.; Umpierrez, Guillermo E.; Gillespie, Charles F.
Abstract: Objective: The purpose of the study was to assess demographic features, rates of trauma exposure, prevalence of post‐traumatic stress and depressive symptoms in a group of urban, low‐income, African‐American women with type 1 or type 2 diabetes mellitus. Research Design and Methods: We conducted a survey of (n = 290) low‐income, African‐American women seeking care in the diabetes clinic of an urban hospital and collected data on the demographic characteristics, childhood and nonchildhood abuse trauma exposure, and the severity of post‐traumatic stress and depressive symptoms using the Post‐traumatic Stress Disorder (PTSD) Symptom Scale (PSS) and the Beck Depression Inventory (BDI). In a subset of women with type 2 diabetes (n = 96), we assessed haemoglobin A1c to examine the relationship between psychopathology and glycaemic control. Results: Of the overall sample, 61.7% reported exposure to trauma in their lifetime, and 30.4% and 29.3% had current PTSD and MDD, respectively. Exposure to both childhood and nonchildhood abuse trauma was associated with an increased PTSD and depressive symptom severity ( P 's < .05). PTSD diagnosis, but not depression, was associated with increased haemoglobin A1c ( P = .002). Conclusions: These data document high levels of trauma exposure, PTSD and depressive symptoms in diabetic African‐American women treated in a specialty clinic of an urban hospital setting. Furthermore, these data indicate that the presence of PTSD is negatively associated with glycaemic control. Abstract : Levels of trauma exposure, post‐traumatic stress disorder (PTSD) and depressive symptoms are high in diabetic African‐American women and adversely impact glycaemic control.